Contribution of atomistic study to better understand water saturation effect on mechanical behavior of clayey rocks in triaxial compression. (June 2022) - Zhu, L.P.; Shen, W.Q.; He, M.C.; Shao, J.F.
Abstract: The mechanical behavior of clayey rocks is generally sensitive to water saturation degree, mainly due to the high content of swelling clay minerals. In this study, the mechanical behavior of Montmorillonite (MMT) crystal with different water content at the atomistic scale is investigated by using molecular dynamics (MD) simulation. In accordance with macroscopic laboratory tests, we consider here triaxial compression with constant mean stress respectively for the dry and hydrated MMT systems containing one, two and three water layers. While whole stress–strain responses are calculated, the emphasis is put on the key mechanisms which are related to water saturation effect on both failure and deformation properties. It is found that the mechanical behavior of a hydrated MMT system is not only dependent on the number but also the arrangement of interlayer water molecules. In particular, the water sensitivity of mechanical behavior is driven by both the clay–solution (water and Na cation mixture) and the solution–solution interactions. It seems that the MMT system with the two-layer hydrated state provides a more stable arrangement of water molecules and has a higher mechanical strength than the other two ones. The results issued from this study brings a microscopic insight onto the water sensitivity of macroscopic deformation and failure properties of clayey rocks.